2003
DOI: 10.1080/00039896.2003.10745072
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Exacerbation of Asthma Symptoms: Findings from a Population-Based Study in Maine

Abstract: In this population-based study of asthma in the State of Maine, the authors investigated how often asthma symptoms were exacerbated in the workplace. Participants from 5 hospital service areas in Maine completed a telephone questionnaire. Of 474 adult participants (18-65 yr of age) employed during the preceding year and for whom information on occupation and industry was available, 64 (13.5%) were identified with current asthma, including 28 (5.9%) with current physician-diagnosed asthma and 36 (7.6%) who met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Additional references were sought from abstracts presented at the 2005 and 2006 conferences of the ATS and the European Respiratory Society. One referenced article appeared in 2005, but was back-dated to 2003 because the journal was filling in missed editions after a temporary suspension of publication [7]. Finally, additional references were accessed based on the author's familiarity with the literature.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Additional references were sought from abstracts presented at the 2005 and 2006 conferences of the ATS and the European Respiratory Society. One referenced article appeared in 2005, but was back-dated to 2003 because the journal was filling in missed editions after a temporary suspension of publication [7]. Finally, additional references were accessed based on the author's familiarity with the literature.…”
Section: Search Strategymentioning
confidence: 99%
“…Four studies used data from questionnaires and medical records [8,9 -11 ], and one of these four also employed clinical tests conducted by the researchers [11 ]. A fifth study used both a questionnaire and clinical tests [12 ], and only one relied exclusively on questionnaire data [7]. All the operational definitions of WEA were based, in part, on reports by participants that conditions at work made their asthma worse or that their asthma improved while away from work.…”
Section: Operational Definitions and Estimates Of Prevalencementioning
confidence: 99%
“…17 From a population based survey conducted in the state of Maine, 25% of 64 adults with asthma reported that their coughing or wheezing was worse at work. 18 Although the existing population based surveys were informative, an in-depth study that used a more rigorous case definition was needed to provide a more accurate estimate of the prevalence of WEA and a better understanding of the circumstances that contributed to this problem. This additional information could then be used to plan preventive actions.…”
mentioning
confidence: 99%
“…41 Conversely, studies that have assessed WEA prospectively among general asthma populations have suggested this to be much more common, occurring in up to 25% of working asthmatics. [44][45][46] However, these patients include those with transient worsening at work that may occur a few times only. Similarly, review of allowed workers' compensation system claims when WEA is compensable, indicate that WEA accounts for over 7 times as many yearly claims as OA, but the majority of allowed claims had few or no days missed from work and only 10% missed 20 days or more from work due to WEA.…”
Section: Epidemiology Of Weamentioning
confidence: 99%